2019
DOI: 10.1186/s12889-019-7610-7
|View full text |Cite
|
Sign up to set email alerts
|

Age moderates the effect of socioeconomic status on physical activity level among south Korean adults: cross-sectional analysis of nationally representative sample

Abstract: BackgroundIn a nationally representative sample of South Korean adults, we investigated the association between socioeconomic status (SES) and physical activity level, and whether this association varied by age group.MethodsWe used data from 5065 subjects aged ≥19 years who participated in the 6th Korea National Health and Nutrition Examination Survey. Weighted logistic regression examined the SES-physical activity association. Using the International Physical Activity Questionnaire short form, physical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…Additionally, participants who earned over USD 6,000 were more satisfied than those earning USD 2,000 to 4,000. The findings regarding education level and household income are consistent with studies that have shown that socioeconomic status is significantly related to physical activity (15)(16). Above all, teenagers' low satisfaction with sports leisure activities is a very severe problem.…”
Section: Satisfaction With Participation In Sports Leisure Activitiessupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, participants who earned over USD 6,000 were more satisfied than those earning USD 2,000 to 4,000. The findings regarding education level and household income are consistent with studies that have shown that socioeconomic status is significantly related to physical activity (15)(16). Above all, teenagers' low satisfaction with sports leisure activities is a very severe problem.…”
Section: Satisfaction With Participation In Sports Leisure Activitiessupporting
confidence: 90%
“…6.02±0.79 *P < 0.05, **P < 0.01, ***P < 0.001 (tested by one-way analysis of variance) Typically, the higher the educational level, the higher the household income level. The study results showed that the higher the educational and household income level, the higher the participation rate in sports leisure activities, aligning with studies that have shown that socioeconomic status and the level of physical activity are significantly related (15)(16). Participants in sports leisure activities showed higher levels of happiness and leisure life satisfaction with leisure activities than participants in non-sports leisure activities.…”
Section: Comparison Of Sports and Non-sports Leisure Activitiessupporting
confidence: 86%
“…Vast research that was done in high income countries showed that socioeconomic status is an important factor to PA [ 65 ]. This concur with our finding, which showed that those earning low income were less likely to engage in adequate PA. A possible explanation may be because those who earned a higher income have better access to exercise facilities, such as membership to the gymnasium [ 65 ]. Higher income can create opportunities for them to buy their own health equipment, which contributes to more PA [ 57 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have shown that sociodemographic correlates of PA participation change with the age of the studied population. 47 Therefore, we selected the middle-aged population for a more homogenous sample of the population. Moreover, as the middle-aged population is a critical age group for the prevention of multiple chronic health conditions, our findings would help to inform health promotion policies for the targeted population.…”
Section: Discussionmentioning
confidence: 99%